Black women on the frontline of the fight for racial justice : Evelyn Williams' Inadmissible evidence - S. Palekar (Law Text Culture, 1995)
Evelyn Williams's Inadmissible Evidence is an amazingly powerful and moving autobiography which charts a magnificent political, psychological, spiritual and philosophical journey. The text cannot fail to have far reaching consequences for a variety of writers and readers, as it speaks clearly and compellingly about extremely complex and painful issues like racism, sexism, discrimination, harassment and minoritisation of people, dominant legal discourses and concepts of "Justice" that often work to uphold the status quo and obliterate those already oppressed because of their race, ethnicity, poverty and gender. It is evident that Evelyn Williams's upbringing, and the love and support she receives from her parents give her the strength to face and overcome the toxic levels of racism and sexism that she encounters. She and her niece JoAnne Chesimard (later known as Assata Shakur), have been socialised from birth to believe in themselves, to believe that their opinions are important, that they have rights, that they are right, that they are a part and product of a long tradition of strong, proud Black women. Thus the autobiography highlights the importance of a strong sense of community, and the significant role that it plays in the survival and success of oppressed minorities. Evelyn Williams's and Assata Shakur's inner strength, fierce will and determination ultimately enables them to rebel against the strictures that are placed on them for their crimes of being Black and female in a White supremacist, patriarchal society. Though their rebellion is expressed in different ways - Shakur steps outside society by becoming a revolutionary, while Williams subverts the legal system from within - their common aim of Black liberation makes their bond even stronger than the blood-bond that already exists, that of aunt and niece.